Late Quaternary Climate Reconstruction and Lead-Lag Relationships of Biotic and Sediment-Geochemical Indicators at Lake Bolshoe Toko, Siberia - Biskaborn, Boris K.; Nazarova, Larisa; Kröger, Tim; Pestryakova, Lyudmila A.; Syrykh, Liudmila; Pfalz, Gregor; Herzschuh, Ulrike; Diekmann, Bernhard (Frontiers in Earth Science, 2021)
Millennial-scale climate change history in eastern Siberia and relationships between diatom diversity, paleoclimate, and sediment-geochemical lake system trajectories are still poorly understood. This study investigates multi-proxy time series reaching back to the Late Pleistocene derived from radiocarbon dated Lake Bolshoe Toko sediment cores, southeastern Yakutia, Russia. We analyzed diatoms, elements (XRF), minerals (XRD), grain-size, organic carbon, and included chironomid analyses and published pollen-data for quantitative paleoclimate reconstruction. Changes in diatom species abundances reveal repeated episodes of thermal stratification indicated by shifts from euplanktonic Aulacoseira to Cyclotella species. Chironomid and pollen-inferred temperature reconstruction reveal that the main shift between these diatom species is related to the onset of Holocene Thermal Maximum (HTM) at 7.1 cal ka BP. Comparison to other paleoclimate records along a north-south transect through Yakutia shows that the HTM was delayed as far south as the Stanovoy mountains. Relationships between sediment-geochemistry, paleoclimate variability and diatom species richness (alpha diversity) was tested in a moving temporal offset approach to detect lead-lag relationships. Sediment-geochemical data, mainly uniform during the Holocene, revealed strongest positive or negative correlations ahead of species richness changes. Mean July air temperature (TJuly) reconstructions correlate with both Hill numbers and relative assemblage changes indicated by sample scores of multidimensional scaling analysis (MDS) over the entire time series. We found that sediment organic carbon revealed distinct positive correlations, i.e. centennial-scale delay to increases in diatom effective richness (Hill numbers N0 and N2). We conclude that a lag of deposited organic carbon concentrations behind changes in diatom alpha diversity reveals that species richness can augment the production and thus sequestration of organic matter in comparable lake systems.